RESIDENTIAL INTERIOR DESIGN CHARACTERISTICS OF THE ANALYSIS IN THE PERIOD - E. Kuldashev (Journal Park Publishing, 2022)
In this article, the main task is to identify the most effective design methods and the sequence of development of a design concept.
Keywords: Pre-project period, author's decision, author's concept, pre-project analysis, colorist, visual inspection